PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU (Madrasah Aliyah Bahrul Ulum Desa Air Emas Kecamatan Singingi) - Titik Kurniawati; Bustanur Bustanur; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Doing education is a complex process. The institution need to improve the quality of education through standardization and professionalization in various components in the education system. Principals are required to be independent and have accountability on it, so they need a transformative character in self. But in reality, so many principals have not even implemented this type of leadership, so there are various kinds of problems that can affect the performance of teachers in schools because their worksphere is not positive. The goals of this research is to determine the effect of madrasah principal’s transformational leadership toward teachers performance in Madrasah Aliyah, Bahrul Ulum, Air Emas, Singingi Sub-district. The type of this research is quantitative associative, more specifically as causal associative. Data processing using simple linear regression formula with SPSS software. This research is located in Madrasah Aliyah Bahrul Ulum, Air Emas, Singingi Subdistrict. The number of samples was 18, and using questionnaires, interviews, observations and documentation to collects the data. The results showed that there was an effect of transformational leadership on teacher performance with the results of F Count> F Table, 2.88> 0.10, Y = 50.807 + 0.391, and by 15% while 85% was effected by other factors that out of the focus on this research. Kata Kunci: petunjuk penulisan; sosial; budaya keislaman